The Role of the VEGF Family in Coronary Heart Disease - Zhou, Yan; Zhu, Xueping; Cui, Hanming; Shi, Jingjing; Yuan, Guozhen; Shi, Shuai; Hu, Yuanhui (Frontiers in Cardiovascular Medicine, 2021)
Vascular endothelial growth factor (VEGF) family, the regulator of blood and lymphatic vessels, is mostly investigated in tumor and ophthalmic field. But the functions it enjoys can also interfere with the development of atherosclerosis (AS) and further diseases like coronary heart disease (CHD). The source, regulating mechanisms including up regulation and down regulation, target cells/tissues and known functions about VEGF-A, VEGF-B, VEGF-C and VEGF-D are covered in the review. VEGF-A can regulate angiogenesis, vascular permeability and inflammation by binding with VEGFR-1 and VEGFR-2. VEGF-B can regulate angiogenesis, redox and apoptosis by binding with VEGFR-1. VEGF-C can regulate inflammation, lymphangiogenesis, angiogenesis, apoptosis and fibrogenesis by binding with VEGFR-2 and VEGFR-3. VEGF-D can regulate lymphangiogenesis, angiogenesis, fibrogenesis and apoptosis by binding with VEGFR-2 and VEGFR-3. These functions present great potential of applying VEGF family for treating CHD. For isntance, angiogenesis can compensate for hypoxia and ischemia by growing novel blood vessels. Lymphangiogenesis can degrade inflammation by providing exits for accumulated inflammatory cytokines. Anti-apoptosis can protect myocardium from impair after myocardial infaction (MI). Fibrogenesis can promote myocardial fibrosis after MI to benefit cardiac recovery. In addition, all these factors have been confirmed to keep a link with lipid metabolism, the research about which is still in early stage and exact mechanisms are relatively obscure. Because few review has been published about the summarized role of VEGF family for treating CHD, the aim of this review article is to present an overview of the available evidence supporting it and give hint for further research.